2020
DOI: 10.14202/vetworld.2020.916-922
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and genetic variability of Ehrlichia canis in pet dogs in Xinjiang, China

Abstract: Background and Aim: As a tick-borne zoonotic pathogen, Ehrlichia canis has already posed a threat to public health and safety. This study aimed to clarify the prevalence and molecular characteristics of E. canis in pet dogs in Xinjiang, China. Materials and Methods: A total of 297 blood samples of pet dogs and 709 skin ticks (Rhipicephalus sanguineus sensu lato) were subjected to molecular detection using PCR for E. canis 16S rRNA gene, and then, positive samples were amplified, sequenced, and phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In the present study, A. platys (16.36%) was the most common canine tick-borne pathogen. The positive animals in this study were similar to the 11% (17/157) reported in dogs in the USA (Kelly et al, 2013), and were lower than those investigated by previous works; for example, 28% (42/150) in Pakistan (Malik et al, 2018) and 12.12% (36/297) in China (Mengfan et al, 2020). In Thailand, our results have exhibited that the occurrences of canine TBP infections of dogs were similar to those reported by previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, A. platys (16.36%) was the most common canine tick-borne pathogen. The positive animals in this study were similar to the 11% (17/157) reported in dogs in the USA (Kelly et al, 2013), and were lower than those investigated by previous works; for example, 28% (42/150) in Pakistan (Malik et al, 2018) and 12.12% (36/297) in China (Mengfan et al, 2020). In Thailand, our results have exhibited that the occurrences of canine TBP infections of dogs were similar to those reported by previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…These species have been detected in many ticks in China, for instance, Amblyomma testudinarium, Haemaphysalis yeni, Haemaphysalis longicornis, Ixodes sinensis, D. silvarum, Rhipicephalus sanguineus, and Rhipicephalus microplus (45)(46)(47)(48). In previous studies, E. canis infection was detected in Cervus nippon in Gansu (49), and high infection rates of E. canis and E. chaffeensis were reported in dogs, cattle, sheep, goats, donkeys, and humans in Xinjiang (9,18,50). Ehrlichia species were also detected in birds and small mammals in other parts of China (51,52).…”
Section: Discussionmentioning
confidence: 93%
“…Although E. canis has a worldwide distribution, regional infection patterns are extremely varied. For example, seroprevalence rates as high as 12.2% have been reported in Xinjiang, China (Mengfan et al., 2020 ) while a rate of 1.33% was reported in Eastern China (Zhang et al., 2017 ). Further afield, E. canis seroprevalence rates appear to be low in Japan (Inokuma et al., 2003 ), North America and the United States (Little et al., 2021 ) but reached 30.83% in Mexico (Movilla et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%